International agricultural research and human nutrition - Pinstrup-Andersen, Per; Berg, Alan; Forman, Martin J. (International Food Policy Research Institute, 1984)
This book presents a comprehensive review of the nutrition-related activities undertaken by the international agricultural research centers (IARCs) supported by or associated with the Consultative Group on International Agricultural Research (CGIAR) and suggests ways in which local, national, and international agricultural research institutions can incorporate goals of improving human nutrition into research design and planning. Because hunger and malnutrition are closely linked with poverty, the content of the book also provides a great deal of evidence of the way the work of the centers relates to the poor, whether farmers, workers, or consumers.